Profit Maximization Through Linear Programming Problem: A Case Study Of Chocolate Making Industry In Karnataka, India - Imran, Dr. Khalid; K S, Dr. Ravi; N, Dr. Raghu; V, Chandan; Prakash, Dr. G V Naveen (Migration Letters, 2024)
Linear programming, a mathematical approach, aims to select the most optimal combination of products to either maximize profits or minimize costs while operating within the constraints of available resources. This article presents the application of linear programming specifically for maximizing profits in a chocolate factory situated in Bengaluru, Karnataka, India. When dealing with linear programming problems, the Simplex algorithm stands out as a robust computational tool, offering rapid solutions even for extensive applications. The focus of optimization in this study cantered on evaluating the unit cost of production, setting selling prices, and determining the quantities of various raw materials utilized in the production process. A model addressing these concerns was formulated, and optimal outcomes were derived through software employing the simplex method. The primary aim of this work is to u[1]nderscore the distinct advantages of employing linear programming as an optimization technique in business operations, specifically urging manufacturing enterprises to consider its implementation for determining the most advantageous path to optimal profits.